A Review on the Mechanism and Application of Keishibukuryogan - Tanaka, Koichiro; Chiba, Koki; Nara, Kazuhiko (Frontiers in Nutrition, 2021)
The concept of “blood stasis” – called yū xiě in Chinese, Oketsu in Japanese – is one of the unique pathophysiology of traditional medicine that originated in China and inherited in Korea and Japan. This concept is related to the multiple aspects of hemodynamic disorders brought on by quantitative and qualitative changes. It theorizes that the quantitative changes of “blood stasis” are related to peripheral circulatory insufficiency. When chronic qualitative changes of “blood stasis” produce stagnant blood that turns into a pathological product, it could cause inflammation and lead to organic changes. Trauma induced hematomas, that are considered to be a quantitative change of blood, are also a form of blood stasis. The basic medicine research on Keishibukuryogan (KBG) –a Japanese name in Traditional Japanese Medicine (Kampo) for one of the most common anti- “blood stasis” prescriptions, also known as gui-zhi-fu-ling-wan (GFW) in Chinese in Traditional Chinese Medicine (TCM) –indicated that the initiation of quantitative changes was closely related to loss of redox balances on endothelial function induced by oxidative stress. The following qualitative changes were related to coagulopathy, hyper viscosity; anti-platelet aggregation, lipid metabolism; a regulation of systemic leptin level and/or lipid metabolism, inflammatory factor; cyclooxygenase-1,2 (COX-1, 2), interleukin-6, 8 tumor necrosis factor-α, macrophage infiltration, hyperplasia, tissue fibrosis and sclerosis caused by transforming growth factor-β1 and fibronectin, the dysfunction of regulated cell deaths, such as, apoptosis, autophagy, ferroptosis and ovarian hormone imbalance. Clinically, KBG was often used for diseases related to Obstetrics and Gynecology, Endocrine Metabolism, Rheumatology and Dermatology. In this review, we give an overview of the mechanism and its current clinical application of KBG through a summary of the basic and clinical research and discuss future perspective.